Reinstatement in Arbitration: The Grievors' Perspective - Williams, Kelley; Taras, Daphne (Relations industrielles / Industrial Relations)

(untitled) (Département des relations industrielles de l'Université Laval, 2000)
Virtually absent in the arbitration literature is the voice of the grievor. We examine post-reinstatement experiences primarily from the perspectives of a group of seven Alberta grievors. We first review the declining frequency of Alberta arbitrations, the extent to which dismissal cases form a proportion of the arbitral caseload, and the relatively low rate of reinstatement. Findings are: (1) grievors are unaware of the public availability of arbitration awards; (2) reinstated grievors are critical of the union that successfully defended them; (3) they have a more benign view of management;(4) very little reinstatement assistance is offered; and (5) grievors' positive attitudes to their worksites are more determinative of successful reinstatement than remorse and acceptance of culpability.